2023
DOI: 10.3390/ijerph20156537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Sports Intervention and the Involvement Level on the Mineral Health of Different Bone Sites in the Leg, Hip, and Spine: A Systematic Review and Meta-Analysis

Thiago P. Oliveira,
Mário C. Espada,
Danilo A. Massini
et al.

Abstract: The current study analysed whether the osteogenic stimuli of exercises and sports have an independent effect on bone mineral density (BMD). Studies with a design having two different cohorts were searched and selected to distinguish the effect due to long-term involvement (i.e., athletes vs. non-active young with good bone health) and due to the planning of intervention (i.e., pre- vs. post-training) with exercises and sports. Moreover, only studies investigating the bone sites with a body-weight support funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Consequently, regional specificity could be noted between strength and LM and bone mass, which was suggested by Matsuo et al [ 31 ] as being a context influenced by hormonal and mechanical stimuli attributed to the action of a larger muscle mass. Previously, the role of regional fat-free tissue for monitoring the muscle strength development in specific body regions [ 27 , 32 ] was also evidenced, and from the current results, this association was also observed at the regional level (e.g., the specificity of the exercise involving a target region), while confirming the aforementioned role of regional and whole-body LM, but now in the context of bone sites with a weightbearing function, such as the femur.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, regional specificity could be noted between strength and LM and bone mass, which was suggested by Matsuo et al [ 31 ] as being a context influenced by hormonal and mechanical stimuli attributed to the action of a larger muscle mass. Previously, the role of regional fat-free tissue for monitoring the muscle strength development in specific body regions [ 27 , 32 ] was also evidenced, and from the current results, this association was also observed at the regional level (e.g., the specificity of the exercise involving a target region), while confirming the aforementioned role of regional and whole-body LM, but now in the context of bone sites with a weightbearing function, such as the femur.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in sport and exercise is typically expected to have positive effects on bone mineral density (BMD). Studies have consistently shown sport (especially weight-bearing activities) positively influences BMD [4,5]. Mechanical loading promotes bone osteoblast proliferation and bone accrual; hence, walking or running increases BMD more than nonweight-bearing activities such as swimming [6].…”
Section: Introductionmentioning
confidence: 99%